Marketing Communication Strategies for IM3 Card in Seeking Teenager as Target of Market in Yogyakarta - Fadeyanto Prabowo (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
Ten operator telecommunication industries in Indonesia fight in competition to get subscribers. These are Telkom, Telkomsel, Indosat, Excelmindo, Hutchison, Sinar Mas, Sampoerna, Bakrie, Telecom, Mobile-8 and Cell Phones Natrindo. They try to grasp market share of subscribers in telecommunication industries. Many still believe that market potential was still opened especially the growth the teenagers as subscriber. Therefore, we can observe that competition to grasp market potential of teenagers was tight position one another. They was racing to qualify their own products so consumers and customers can think, perceive and make decision to purchase their needs in related to telecommunication products. Indosat as one important of player within industries always tries to improve the sales volume of the product including the IM3 Card. Therefore, at this point, this research was to know how marketing communication strategies do segment IM3Card for the teenagers as the potential market in Yogyakarta. Data was obtained by interviews, observation and document analysis. The result show us that many strategies of creative that was developed based on research and trends of teenagers lifestyle.